2012
DOI: 10.1016/j.brainres.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre- and postnatal protein malnutrition in hypoxic–ischemic rats

Abstract: Neonatal hypoxic-ischemic encephalopathy (HI) is a major cause of nervous system damage and neurological morbidity. Perinatal malnutrition affects morphological, biochemical and behavioral aspects of neural development, including pathophysiological cascades of cell death triggered by ischemic events, so modifying resulting brain damage. Female Wistar rats were subjected to protein restriction during pregnancy and lactation (control group: 25% soybean protein; malnourished group: 7%). Seven days after delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 42 publications
2
25
0
2
Order By: Relevance
“…In this study, we adapted a number of behavioral tests, including the geotaxis reflex (Sanches et al, 2012), cliff avoidance reaction (Bouslama et al, 2007) and grip test (Liu et al, 2013) to test whether HPC improves motor functional recovery after HI. In addition to the morphological evidence from TTC staining at 24 h and brain histology at 7 days post-HI, we reported that HPC improved functional and behavioral recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we adapted a number of behavioral tests, including the geotaxis reflex (Sanches et al, 2012), cliff avoidance reaction (Bouslama et al, 2007) and grip test (Liu et al, 2013) to test whether HPC improves motor functional recovery after HI. In addition to the morphological evidence from TTC staining at 24 h and brain histology at 7 days post-HI, we reported that HPC improved functional and behavioral recovery.…”
Section: Discussionmentioning
confidence: 99%
“…These tests evaluated: 1) geotaxis reflex (Sanches et al, 2012) to evaluate vestibular and/or proprioceptive functions; 2) cliff avoidance reaction (Bouslama et al, 2007) to check for the presence of maladaptive impulsive behavior; and 3) grip ability (Liu et al, 2013) to assess grip force and fatigability. After completion of the tests, mice were deeply anesthetized with isoflurane and their brains were removed and fixed with 4% paraformaldehyde in PBS for immunohistochemical evaluation.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…We also considered protein adequacy, since protein malnutrition during pregnancy and lactation results in impaired sensorimotor function after neonatal cerebral hypoxia ischemia. 51 In both groups of pups, weight gain was the same (Table 2), as was serum protein. Although blood glucose was higher in HF progeny at P35, this was not the case at P14; moreover, hyperglycemia reportedly does not increase the severity of hypoxic-ischemic damage in the neonatal rodent brain.…”
Section: Discussionmentioning
confidence: 92%
“…Brain damage was reflected by a deficit in the wet weight of the ipsilateral (left) ischemic hemisphere and is expressed as a percentage of the wet weight of the contralateral (right) control hemisphere [19,20]. This method of assessing the developing brain damage in a rat model of HI has recently been used by a number of other research groups [8,17,30]. Our previous control experiments demonstrated equal weight of the left and right hemisphere in naive and sham-operated animals and that H-I induction in 7-day-old rats does not interfere with the mass of the contralateral (reference) hemisphere.…”
Section: Methodsmentioning
confidence: 99%